PENGGUNAAN BAHASA INDONESIA DALAM INTERAKSI KELAS MATA PELAJARAN BAHASA INDONESIA (STUDI KASUS DI SMA NEGERI 2 SRAGEN) - Dina Handayani; Sarwiji Suwandi; Budhi Setiawan (Universitas Sebelas Maret, 2019)
This research aims to describe and explain: (1) the conversation structure in the classroom interaction of Indonesian language subject between teachers-students and among students and (2) the language function of the teachers' language and students' language in the classroom interaction. This research was conducted at SMA Negeri 2 Sragen. The subjects of this study were the use of language the teacher and students in Indonesian language course. The data in the form of sentences and discourse were analyzed by Sinclair & Cotlthard (1975) theory and Halliday (1973) theory. This research belongs to qualitative research using case study methods. The results of this study are; first, in the teachers-students conversation structure and the students-students conversation structure found new actions, namely, repeat. Both of the sequences of the conversation structure unit are from the largest to the smallest, namely: lesson, transaction, exchange, move, and act. Second, the language functions in the teachers’ language and students’ language, namely: the instrumental function, the regulatory function, the interaction function, the representational function, the personnel function, and the heuristic function.